Analysis of Physico-Chemical Profiles of Penna River Water at Selected Areas of Nellore District, Andhra Pradesh. - Madhavi Somu,; Dr. Suseela Meesala, (The Bioscan, 2026)
Freshwater ecosystems act as dynamic realms that profoundly influence aquatic life forms and display significant seasonal swings in their physicochemical properties, yet these natural cycles are increasingly disrupted by accelerated urbanization, industrial development, and diverse anthropogenic influences such as the direct release of untreated or poorly treated domestic sewage coupled with agricultural effluents into the water bodies. This particular research delves into these modifications over the pre-monsoon, monsoon, and post-monsoon periods in the River Penna situated in Andhra Pradesh's Nellore region, where measured variables included temperature, pH, dissolved oxygen (DO), total dissolved solids (TDS), total suspended solids (TSS), alkalinity, hardness, and nutrient levels encompassing phosphates and nitrates, revealing distinct seasonal signatures in the findings.